QbD Approach for Developing Fast-Dissolving Films of Ondansetron Hydrochloride using HPMC E5 and Primojel - Shankar, Kunderu Ravi; Gunda, Raghavendra Kumar; Babu, Rayavarapu Sanjay; Eswar, Pothuri Srinivasa; Avvari, Sathvika; Lakshmi, Kollipara Naga Venkata Chenchu; Aminabee, Shaik (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: Purpose of present research study was to use Ondansetron to develop a film that dissolves quickly. Materials and Methods: HPMC E5 and Primojel were used in different ratios to prepare oral dissolving films. Technique used to prepare films was solvent casting. Results: Because of HPMC E5 cps, the film had an excellent thickness. The plasticizer glycerin showed good folding durability, elongation percentage, and tensile strength. Formulation F7 showed better oral sensation, folding capacity, and enhanced release of drug from formulation. The F7 had a quicker disintegration time of 31 sec and delivered 100% of the drug in 2 min. Percentage (%) and time of disintegration of drug thawed after 2 min (PD2) was calculated using polynomial equations created with Design Expert 7 software. To calculate the time of disintegration (Y1) and drug percentage dissolved in 2-min (Y2), the following formulas were utilised. For DT, Y1 is equal to 54.109 + 8.829 X1-19.828 X2-2.76 X1X2-0.169 X12+4.832 X22; for PD2, Y2 is equal to 59.98-1.769 X1+6.832 X2+ 0.39 X1X2+0.59 X12-3.59 PD22. Because the X1 coefficient in equation Y1 had a positive sign that predicts disintegration time increases as the HPMC content increases. In equation Y1 if X2 coefficient is negative it indicates when primojel concentration increases, the disintegration time decreases. Conclusion: Thus, using HPMC E5 and primojel, ondansetron mouth dissolving films were effectively prepared using a 32 Factorial Design. F7 formulation, which contains HPMC E5 (500 mg) and Primojel (5 mg), was deemed best formulation based on attractiveness.
Keywords: Ondansetron; HPMC E5; Primojel; 3² Factorial Design; solvent-casting; Fast-Dissolving; Film; Disintegration Time